Inovasi Beton Ramah Lingkungan Dengan Pemanfaatan Limbah Kaca dan Plastik PET - Ramadhan, Deni; Wahyudi, Ismail; Afiah, Alfiana; Arcana, Gusti Putu Febri; Rizky, Muhammad; Istanto, Kelik (Indonesian Society of Applied Science, 2024)
Nowadays, the use items made from glass and plastic has increased, causing accumulation. One of them is Bakung landfill in Bandar Lampung which accommodates 1,000 tons per day. Accumulating glass and plastic waste has caused various environmental problems. This research was carried out as form of technological innovation and effort to preserve environment due to this waste. The research purpose is finding environmentally friendly concrete formula by substituting glass waste and PET plastic but have characteristics that comply with SNI standards. Each material that makes up the concrete is tested for its characteristics so that normal concrete mix design can be carried out. Glass waste and PET plastic are substituted at 10%, 15%, and 25% into coarse and fine aggregate formulations in normal concrete formula, thereby creating variations in test specimen. The concrete sample has made in cube with dimensions of 15 x 15 x 15 cm. Concrete compressive strength tests were carried out at 7, 14, 21 and 28 days. Compressive results strength test showed that variations in substitute materials in concrete have effect on resulting compressive strength. Concrete test results with 10% and 15% substitution have compressive strength values ​​that was close to each other and higher than 25% substitution. Even though the two compositions have close compressive strength values, they have different standard deviations. The standard deviation values ​​for 10% and 15% substitution have 35.9913 and 23.1299. So, concrete with 15% substitution composition was the most optimal composition because it showed most dominant advantage among others.